Origin of the transition voltage in gold-vacuum-gold atomic junctions - SANVITO, STEFANO (My University, 2013)
The origin and the distance dependence of the transition voltage of gold–vacuum–gold junctions are investigated by employing first-principles quantum transport simulations. Our calculations show that atomic protrusions always exist on the electrode surface of gold–vacuum–gold junctions fabricated using the mechanically controllable break junction (MCBJ) method. The transition voltage of these gold–vacuum–gold junctions with atomically sharp electrodes is determined by the local density of states (LDOS) of the apex gold atom on the electrode surface rather than by the vacuum barrier shape. More specifically, the absolute value of the transition voltage roughly equals the rising edge of the LDOS peak contributed by the 6p atomic orbitals of the gold atoms protruding from the electrode surface, whose local Fermi level is shifted downwards when a bias voltage is applied. Since the LDOS of the apex gold atom depends strongly on the exact shape of the electrode, the transition voltage is sensitive to the variation of the atomic configuration of the junction. For asymmetric junctions, the transition voltage may also change significantly depending on the bias polarity. Considering that the occurrence of the transition voltage requires the electrode distance to be larger than a critical value, the interaction between the two electrodes is actually rather weak. Consequently, the LDOS of the apex gold atom is mainly determined by its local atomic configuration and the transition voltage only depends weakly on the electrode distance as observed in the MCBJ experiments.
PUBLISHED
Keywords: Physics; Nanoscience & Materials